1999
DOI: 10.1128/aem.65.12.5504-5509.1999
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Transcription Studies of the Dextransucrase Gene in Leuconostoc mesenteroides NRRL B-512F

Abstract: Dextransucrase production by Leuconostoc mesenteroidesNRRL B-512F in media containing carbon sources other than sucrose is reported for the first time. Dextransucrases were analyzed by gel electrophoresis and by an in situ activity assay. Their polymers and acceptor reaction products were also compared by 13C nuclear magnetic resonance and high-performance liquid chromatography techniques, respectively. From these analyses, it was found that, independently of the carbon source, L. mesenteroides NRRL B-512F pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Fructose accumulation has been previously described for dextran producing Lc. mesenteroides strains (Dols, Chraibi, Remaud-Simeon, Lindley & Monsan, 1997;Quirasco, López-Munguía, Remaud-Simeon, Monsan & Farrés, 1999;Santos, Teixeira & Rodrigues, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Fructose accumulation has been previously described for dextran producing Lc. mesenteroides strains (Dols, Chraibi, Remaud-Simeon, Lindley & Monsan, 1997;Quirasco, López-Munguía, Remaud-Simeon, Monsan & Farrés, 1999;Santos, Teixeira & Rodrigues, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The di¤culties in identifying a protease in DS preparations allowed the hypothesis of the existence of 57^62 kDa subunits of DS [5^7]. It has recently been reported that the L. mesenteroides B-512F DS gene is located in a monocistronic operon [19]. The L. mesenteroides NRRL B-512F DS gene sequence encodes 1527 amino acids including the signal peptide [20], resulting in a predicted 170 kDa protein, that upon elimination of the signal peptide would be reduced to 166 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, the soluble GTF fraction was precipitated from the supernatant cultures by the addition of one volume of 50% (w/v) polyethylene glycol 5000 and centrifugation (7,000 × g , 5 min at 4°C). The pellet of cells containing the cell-associated GTF fraction, was washed three times and resuspended in a minimal volume of 0.1 mM, pH 5.4 acetate buffer (Quirasco et al 1999 ). Polymer was produced in both fractions in the same buffer conditions containing 10% sucrose in final volume of 600 μL and incubated at 30°C and 100 rpm for 14 h (New Brunswick Scientific G24 shaker).…”
Section: Methodsmentioning
confidence: 99%